HUBUNGAN SELF MANAGEMENT BEHAVIOR DAN SELF EFFICACY DENGAN RESILIENSI PASIEN HEMODIALISA - Dwi Retno Sulistyaningsih; Retno Setyawati; Arum Zahrotul Niswah (Universitas Muhammadiyah Klaten, 2025)
Background: Hemodialysis patients are faced with various complex challenges, both physical, psychological and social, as a result of chronic kidney failure and ongoing therapeutic procedures. However, the ability of hemodialysis patients to manage themselves is still not optimal because some patients are less compliant with treatment and lack self-confidence. This condition can affect their ability to adapt to stressful situations, so resilience becomes an important aspect in facing these challenges. Method: This research uses quantitative methods with a correlational design and a cross sectional approach. Data collection was carried out using a questionnaire. The number of sample in this research was 82 people using a total sampling technique. Data were processed statistically using the Gamma test. Result: based on the results of the analysis, it was found that the majority of respondents were female (58,5%), with the average age of respondents being 51,60 years old, the average length of time respondents underwent hemodialysis was 18,13 months, and the majority of respondents had graduated from elementary school (40,2%). The research result also showed that the most self management behavior were those with good self management behavior (70,7%), the respondents with the most self efficacy were those with good self efficacy (81,7%), and the respondents with the most resilience were those with good resilience (81,7%). Conclusion: there is a significant relationship between relationship between self management behavior and self efficacy and the resilience of hemodialysis patients at RSI Sultan Agung Semarang (p value<0,05 and r values 0,595 and 0,803).